2022
DOI: 10.1002/ejp.1933
|View full text |Cite
|
Sign up to set email alerts
|

Unpleasant olfactory and gustatory stimuli increase pain unpleasantness in patients with chronic oral burning pain: An exploratory study

Abstract: Background: Despite mounting evidence for the powerful influence of smell and taste substances in experimental pain, our knowledge of their effects in the clinical context is scarce, especially for patients with chronic oral burning pain.To fill this gap, we investigated the effect of olfactory and gustatory stimuli on pain perception in patients with chronic oral burning pain, a disabling condition that is difficult to manage and treat.Methods: Twenty-two patients with chronic oral burning pain underwent test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Higher pain perceptions have been linked to higher RPE values [ 41 ]. Furthermore, unpleasant tastes may result in potentiated pain responses [ 42 , 43 ]. It is plausible that the NPT resulted in greater exercise-induced hyperalgesia thereby resulting in increases in RPE.…”
Section: Discussionmentioning
confidence: 99%
“…Higher pain perceptions have been linked to higher RPE values [ 41 ]. Furthermore, unpleasant tastes may result in potentiated pain responses [ 42 , 43 ]. It is plausible that the NPT resulted in greater exercise-induced hyperalgesia thereby resulting in increases in RPE.…”
Section: Discussionmentioning
confidence: 99%
“…A prior study reported that smell and taste appear to interact at both the behavioural and neural levels, share common features, and are strongly linked to emotion and cognition [22] . Although there is evidence that olfactory and gustatory substances have powerful effects on experimental pain, such as unpleasant chemosensory stimuli, which increase the perception of pain in patients with chronic oral burns [23] , other studies have reported that olfactory input stimulated by linalool odour has an analgesic effect [24,25] . Currently, nonsteroidal anti-in ammatory drugs (NSAIDs) are most commonly used to relieve pain because they block the formation of arachidonic acid during the prostaglandin production cycle [26] .…”
Section: Introductionmentioning
confidence: 99%